Front Matter Jurnal Litbang Industri Vol. 9 No. 1 Juni Tahun 2019 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2019)
Front Matter Jurnal Litbang Industri Vol. 9 No. 1 Juni Tahun 2019